Dualisme dalam Kesatuan untuk Mencapai Ma'rifah Perspektif KH. Asrori Ishaqi - Muhammad Rahmatullah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2016)
The article reveals the concept of dualism in unity along with ma'rifah in KH. Asrori Ishaqi’s perspective. This article finds that dualism in unity to reach ma'rifah in Kiai Asrori’s perspective rests in his conception about God through what so-called al-Aḥad and al-Wâḥid as well as al-Wujûd and al-Kawn. He emphasizes that there is no al-Wujûd (existence) but Allah’s. It is, therefore, all creatures’ existence is embraced within God’s existence. Al-Kawn—on the other side—is everything which exists and will exist, in which God has known them already and determined their fate. The concept of al-Aḥad emphasizes that Allah is All The One in His Essence in advance of His Asmâ’ (Names) and Attributes. Al-Wâḥid means All The One in His Asmâ’ and Attributes after the emanation of the two over His creatures. In accordance with human’s existence, Kiai Asrori states that humans are created from spiritual realm and the physical one. It seems that Kiai Asrori would emphasize that though Allah is The Almighty and unreachable, the humans can still—in another dimension—reach Him through the emanation of His Asmâ’ with murâqabah using their reasons, understanding, and hearts. Kiai Asrori is an advocate to monistic Sufism and at the same time he also a proponent of dualistic Sufism.